Resilience and Hopelessness in Turkish Society: Exploring the Role of Spirituality in the COVID-19 Pandemic - Hakan Gülerce; Hafza Aroosa Maraj (Journal of Economy Culture and Society)
COVID-19 is an infectious disease that first appeared in China, and turned into a global pandemic. It has affected the health of millions of people and has also driven many changes in societies. This research aims to describe and define the importance of “spirituality” as a mediator in the COVID-19 Pandemic in Turkey while having a positive correlation with “resilience” and an inverse relationship with “hopelessness.” The correlational research design was used and data were gathered through the technique of convenience sampling. Standardized sociological and psychological instruments were used to measure the variables. The participants were (N=546) from the general Turkish population (male and female) with the age range of 20-69. The outcomes revealed that resilience is positively correlated with spirituality (r=0.83, p<0.01), while spirituality is negatively correlated with hopelessness (r=-0.81, p<0.01). Resilience is also negatively correlated with hopelessness (r=-0.72, p<0.01). This study concluded that spirituality has a substantial impact on resilient behavior and reduces hopelessness even globally. This study enhances the literature related to psychological and sociological research and promotes the role of spiritual coping strategies, especially in the state of uncertainty created by the current COVID-19 Pandemic.